Pentingnya Pendidikan Karakter dalam Lingkungan Keluarga - Henra Saputra Tanjung; Florianus Aloysius Nay; Ilmar Andi Achmad (Journal of Education Sciences: Fondation & Application, 2023)
Abstrak This research aims to collaborate and reveal how the importance of character education in the family environment. Method usedin this research is qualitative by using a based approach bibliography, namely looking for references through articles and other sources that are deemed relevant and representative. The results of the study and discussion show that character education has existed since the pre-independence era, but no termed so but education of character, morals, and Pancasila. Term character education has become popular since 2010 during the post-reform era; Character education during the pre-national character development policy was not yet fully framed in the National education system. Educational context character in national education is still implied from based education culture, pancasilais and religion. The implementation has not yet been regulated comprehensive. Meanwhile, after the national character building policy, character education has become a hallmark of the national education system, and the implementation is regulated in detail starting from the implementation strategy, to the stage evaluation.